2019
DOI: 10.1186/s12889-019-7790-1
|View full text |Cite
|
Sign up to set email alerts
|

Maternal exposure to PM2.5 may increase the risk of congenital hypothyroidism in the offspring: a national database based study in China

Abstract: BackgroundMaternal exposure to air pollution is related to fetal dysplasia. However, the association between maternal exposure to air pollution and the risk of congenital hypothyroidism (CH) in the offspring is largely unknown.MethodsWe conducted a national database based study in China to explore the association between these two parameters. The incidence of CH was collected from October 1, 2014 to October 1, 2015 from the Chinese Maternal and Child Health Surveillance Network. Considering that total period o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 40 publications
(27 reference statements)
3
21
0
1
Order By: Relevance
“…The average exposure values of AQI, PM 2.5 , PM 10 , SO 2 , NO 2 CO, and O 3 from 2015 to 2018 in Xi’an city were estimated based on hourly average exposure levels by the weighted average method. Generalized additive model (GAM) fitting in the Gaussian distribution was performed to evaluate the nonlinear relationship of air pollution exposure and birth weight (Shang et al 2019 ). After fitting the related confounders, including maternal age, gestational age ethnicity, and pregnancy season, the degrees of freedom of confounders were calculated by using the Akaike information criterion (AIC).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average exposure values of AQI, PM 2.5 , PM 10 , SO 2 , NO 2 CO, and O 3 from 2015 to 2018 in Xi’an city were estimated based on hourly average exposure levels by the weighted average method. Generalized additive model (GAM) fitting in the Gaussian distribution was performed to evaluate the nonlinear relationship of air pollution exposure and birth weight (Shang et al 2019 ). After fitting the related confounders, including maternal age, gestational age ethnicity, and pregnancy season, the degrees of freedom of confounders were calculated by using the Akaike information criterion (AIC).…”
Section: Methodsmentioning
confidence: 99%
“…As the most sensitive populations, pregnant women and newborns are more vulnerable to the adverse effects of ambient air pollution. Some epidemiological studies indicated that maternal exposure to air pollution had adverse effects on infant health, such as adverse birth outcome and respiratory and neurodevelopmental effects (Backes et al 2013 ; Forns et al 2018 ; Korten et al 2017 ; Pedersen et al 2017 ; Shang et al 2019 ; Yorifuji et al 2015 ). Among them, birth weight is one of the most important predictors of morbidity and mortality in neonates and childhood and adult morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Disease and economic afford from adverse pregnancy outcomes caused by air pollution was enormous which should be valued. Until now, researches on air pollution during pregnancy were mainly focused on maternal complications, fetal development, and congenital malformation; limited studies paid attention to metabolic diseases such as newborn congenital hypothyroidism (CH) (Li et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…This corresponds to almost one in eight deaths globally (http://www.who.int/phe/health_ topics/outdoorair/databases/FINAL_HAP_AAP_BoD_24March2014.pdf?ua=1). Epidemiological and clinical studies have demonstrated that exposure to air pollution, and particulate matter (PM 10 and PM 2.5 ) in particular, is associated with childhood diseases such as allergy, asthma and congenital hypothyroidism and increases the risks once a disease has been contracted [13][14][15]. These findings suggest that essential air pollution sources, such as nitrogen dioxide (NO 2 ), ozone (O 3 ) and sulphur dioxide (SO 2 ) could also contribute to HDMF outbreaks.…”
Section: Introductionmentioning
confidence: 99%